Integrated service post quality improvement to tackle stunting during the COVID-19 pandemic: Lessons learned from Ngemplak-1 Health Center - Utami Putri Kinayungan (BKM Public Health and Community Medicine, 2021)
Objective: This study examines health system strengthening through integrated service post quality improvement to tackle stunting during the COVID-19 pandemic at the Ngemplak-1 Health Center. Content: The COVID-19 pandemic is thought to increase the prevalence of stunting because many families have lost their income so that the toddlers from underprivileged families are unable to access nutritious food. Furthermore, limited access to health facilities during pandemics can reduce stunting detection and delay interventions. The proposed program initiative is improving the integrated service post through community nutrition package components. The first component is to improve the skills of cadres in growth monitoring. Many cadres make mistakes in measuring weight and height. The second component is to improve the capacity of cadres to provide nutrition education and feedback by nutritionists. The third component is improvement team formation. The fourth component is the delivery of protein source packages for stunted toddlers, short and below the red line from underprivileged families. The fifth is to cooperate with the Department of Animal Husbandry and Fisheries to create mini animal husbandry or pond for each integrated service post. The stakeholders of husbandry and fisheries are parents of toddlers who come from underprivileged families or parents who lost their income due to the COVID-19 pandemic. All fundings for these components are taken from the APBDes based on the Permenkeu 61/PMK.07/2019, village funds to support the implementation of integrated stunting prevention intervention activities. The challenge of that component is the commitment of cadres, nutritionists, community midwives, and village government. Improving the skills of cadres as the front line and cross-sector collaboration could be an effective strategy to tackle stunting through community-based interventions.